Radiofrequency ablation in patients with large cervical heterotopic gastric mucosa and globus sensation: Closing the treatment gap. Issue 2 (3rd October 2017) - Kristo, Ivan; Rieder, Erwin; Paireder, Matthias; Schwameis, Katrin; Jomrich, Gerd; Dolak, Werner; Parzefall, Thomas; Riegler, Martin; Asari, Reza; Schoppmann, Sebastian F.
Abstract : Background and Aim: Symptomatic cervical heterotopic gastric mucosa, also known as cervical inlet patch (CIP), may present in various shapes and causes laryngopharyngeal reflux (LPR). Unfortunately, argon plasma coagulation, standard treatment of small symptomatic CIP, is limited in large CIP mainly because of concerns of stricture formation. Therefore, we aimed to investigate radiofrequency ablation (RFA), a novel minimally invasive ablation method, in the treatment of CIP focusing on large symptomatic patches. Methods: Consecutive patients with macroscopic and histological evidence of large (≥20 mm diameter) heterotopic gastric mucosa were included in this prospective trial. Primary outcome was complete macroscopic and histological eradication rate of CIP. Secondary outcome measures were symptom improvement, quality of life, severity of LPR and adverse events. Results: Ten patients (females, n = 5) underwent RFA of symptomatic CIP. Complete histological and macroscopic eradication of CIP was observed in 80% (females, n = 4) of individuals after two ablations. Globus sensations significantly improved from median visual analog scale score 8 (5–9) at baseline to 1.5 (1–7) after first ablation and 1 (1–2) after final evaluation ( P < 0.001). Mental health scores significantly increased from 41.4 (± 8.5) to 54.4 (± 4.4) after RFA ( P = 0.007). LPR improved significantly ( P = 0.005) with absence of strictures after a mean follow up of 1.9 (± 0.5) years. Conclusions: This is the first study on RFA focusing on therapy of large symptomatic heterotopic gastric mucosa. Hereby, we demonstrate that this new technique can be successfully implemented in patients where treatment was limited so far (NCT03023280).